Cation-induced molecular motion of spring-like [2]catenanes - Leontiev, A; Serpell, C; White, N; Beer, P (2011)
The syntheses and cation recognition studies of two novel heteroditopic [2]catenanes that are capable of reversible rotary motion are described. Prepared by chloride anion templation, both catenanes possess a calixdiquinone unit able to bind Na+, K+, NH4+ and Ba2+ cations. Following characterization of thesalts of both catenanes by NMR, mass spectrometry and crystal structure determination, hexafluorophosphate salts were investigated for their behaviour upon addition of cations. Ba2+ complexation caused a partial intra-ring rotation of the two macrocycles in both species, which was reversed upon addition of the sequestering SO42- anion. © The Royal Society of Chemistry 2011.